(untitled) (Journal of Ideas in Health, 2024)
Background: Recurrent aphthous stomatitis (RAS) is a prevalent inflammatory condition, that manifests as mouth ulcers. This study aims to evaluate IL-2 and IL-22 levels in saliva samples of individuals with recurrent aphthous stomatitis (RAS) compared to healthy volunteers. Methods: A case-control study was conducted between April 1st and September 30th, 2023, at the Dental Center of New Baquba, Diyala, Iraq. Saliva samples were collected from 40 patients diagnosed with recurrent aphthous stomatitis and 40 healthy controls. IL-2 and IL-22 levels were assessed in both groups using enzyme-linked immunosorbent assay (ELISA). Statistical analysis, employing paired sample ‘t’ test, was conducted with a significance threshold below. Results: In the case group, the mean age was 53.4 years (SD=1.58), ranging from 26 to 81 years, while in the control group, it was 47.18 years (SD=1.55), ranging from 24 to 78 years. Females predominated in both groups, comprising 62.5% in cases and 52.2% in controls. Most aphthous ulcers (77.5%) were found in the buccal mucosa, with minor aphthous ulcers being the most common (67.5%). Results from paired-samples t-tests revealed significantly higher levels of IL-2 in RAS cases (M=62.090, SD=20.242) compared to controls (M=36.366, SD=14.596), (t(39)=7.101, p < 0.001). Similarly, IL-22 levels were significantly elevated in RAS cases (M=106.537, SD=44.112) compared to controls (M=73.399, SD=32.852), (t(39)=3.553, p=0.001). These results suggest a potential association between RAS and increased IL-2 and IL-22 levels, indicating their involvement in RAS pathophysiology. Conclusion: In summary, females showed a significant predominance in RAS cases. Significant differences were observed in IL-2 and IL-22 levels between case and control groups.